Identifying the Potential for Robotics to Assist Older Adults in Different Living Environments - Mitzner, Tracy L. (2013)
As the older adult population grows and becomes more diverse, so will their needs and preferences for living environments. Many adults over 65 years of age require some assistance [1, 2]; yet it is important for their feelings of well-being that the assistance not restrict their autonomy [3]. Not only is autonomy correlated with quality of life [4], autonomy enhancement may improve functionality [2, 5]. The goal of this paper is to provide guidance for the development of technology to enhance autonomy and quality of life for older adults. We explore the potential for robotics to meet these needs. We evaluated older adults' diverse living situations and the predictors of residential moves to higher levels of care in the United States. We also examined older adults' needs for assistance with activities of daily living (ADLs), instrumental activities of daily living (IADLs), and medical conditions when living independently or in a long-term care residence. By providing support for older adults, mobile manipulator robots may reduce need-driven, undesired moves from residences with lower levels of care (i.e., private homes, assisted living) to those with higher levels of care (i.e., skilled nursing).